2019
DOI: 10.1016/j.colegn.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Use of advance care directives for individuals with dementia living in residential accommodation: A descriptive survey

Abstract: Background: Background: End-of-life decision-making for individuals living with a dementia needs to be addressed because as dementia progresses, individuals need support to make decisions about their health care, living arrangements and end-of-life care changes. Advance care directives (ACDs) provide an opportunity for individuals living with a dementia to communicate their wishes about these important issues. Aim: Aim: The aim of this study was to understand how Australian registered nurses (RNs) use ACDs for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The ACP has gained greater prominence with wider implementation among the community setting in Singapore, including NHs, as it facilitates early discussion about NH residents' wishes for either life-sustaining curative treatment or comfort care in the event of futile treatment during acute deterioration ( Cheng et al, 2020 ). Instead of serving as a tool for NH nurses to preserve residents' autonomy over their care preferences and reduce unnecessary escalation of care and hospitalisations ( Sussman et al, 2020 ), our findings, in congruence with existing literature ( Laging et al, 2015 ;Masukwedza et al, 2019 ;Trahan et al, 2016 ), showed that ACP did not guide NH staff in transfer decisions during residents' acute deterioration. In fact, in this study, the ACP was found to create further ambiguity for NH nurses when residents' ACP preferences conflicted with other considerations -families' wishes, physicians' decisions, and even the staff's own beliefs and values about EOL care.…”
Section: Discussionsupporting
confidence: 78%
“…The ACP has gained greater prominence with wider implementation among the community setting in Singapore, including NHs, as it facilitates early discussion about NH residents' wishes for either life-sustaining curative treatment or comfort care in the event of futile treatment during acute deterioration ( Cheng et al, 2020 ). Instead of serving as a tool for NH nurses to preserve residents' autonomy over their care preferences and reduce unnecessary escalation of care and hospitalisations ( Sussman et al, 2020 ), our findings, in congruence with existing literature ( Laging et al, 2015 ;Masukwedza et al, 2019 ;Trahan et al, 2016 ), showed that ACP did not guide NH staff in transfer decisions during residents' acute deterioration. In fact, in this study, the ACP was found to create further ambiguity for NH nurses when residents' ACP preferences conflicted with other considerations -families' wishes, physicians' decisions, and even the staff's own beliefs and values about EOL care.…”
Section: Discussionsupporting
confidence: 78%
“…The literature on the involvement of care partners in EOL care appears mainly limited to advance directives and advance care planning, and is not specific to the last days and hours (Ampe et al, 2016;Biola et al, 2010;Bollig et al, 2015;Dreyer et al, 2009;Gjerberg et al, 2015;Kirsebom et al, 2017;Masukwedza et al, 2019;Percival & Johnson, 2013;Romøren et al, 2016;Thoresen & Lillemoen, 2016;van Soest-Poortvliet et al, 2014). Regarding the last month of life, Williams et al (2012) mention that care partners are involved in ADLs, such as hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a literature review (n = 24) supported by Andershed and Ternestedt (2001)'s theory, studies offer only a superficial glance at the involvement of care partners in the EOL care of older adults in LTCHs (Auclair & Bourbonnais, 2020). This involvement is almost exclusively described in terms of care planning and decision-making (Ampe et al, 2016;Biola et al, 2010;Bollig et al, 2015;Dreyer et al, 2009;Gjerberg et al, 2011Gjerberg et al, , 2015Kirsebom et al, 2017;Masukwedza et al, 2019;Percival & Johnson, 2013;Romøren et al, 2016;Sarabia-Cobo et al, 2016;Thoresen & Lillemoen, 2016;van Soest-Poortvliet et al, 2014). Only one descriptive correlational study explored other ways care partners are involved in care (e.g., monitoring, personal hygiene, meals).…”
mentioning
confidence: 99%
“…If PLWD were able to receive ACP, the process of collecting the information for future use by their healthcare proxy depends on various factors: 1) the ACP practitioner's efficacy from training, 2) tools and communication used to present the conversation of ACP, and 3) the specific form used to document the ACP discussion by the executor or patient (Denning et al, 2019;Masukwedza et al, 2019;and Sellars et al, 2019). ACP has been found to be a contributing factor in providing positive outcomes found in the SDM process because of ACP's ability to frame the conversation around future health care decisions and educate PLWD patients in completing the documentation or AD (Gotanda et al, 2022 andHuang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…ACP has been found to be a contributing factor in providing positive outcomes found in the SDM process because of ACP's ability to frame the conversation around future health care decisions and educate PLWD patients in completing the documentation or AD (Gotanda et al, 2022 andHuang et al, 2021). Yet, the documents ultimately pose an important role in how the information is presented during SDM (Masukwedza et al, 2019). From a capability approach, the completed document is its legacy for future use by the PLWD's care teams and healthcare proxies.…”
Section: Introductionmentioning
confidence: 99%